Physical activity and screen time in preschool children in Croatia - Brumnić, Vesna (Annales kinesiologiae (Koper), 2025)
This research investigates how disparities in physical activity and screen time among preschoolers can be influenced by parental education and involvement, as well as the involvement of the extended family in child-rearing. The study involved 231 parents who provided information about their children from the three (out of four) re-gions in Croatia. The analysis revealed statistically significant differences in children’s screen time based on the parents’ educational level (p<0.000) and involvement in joint physical activity (p<0.000). No differences were found in the children’s screen time or physical activity depending on the involvement of extended family members (grandpar-ents). Less screen time does not automatically mean higher levels of physical activity in preschool children. It is essential to determine the factors that influence physical activ-ity in preschool children and the time they spend in front of screens
Keywords: čas pred zaslonom; družina; family; Predšolski otroci; preschool children; screen time; Šport; telesna dejavnost otrok